PENEGAKAN HUKUM YANG BERKEADILAN SOSIAL DAN BERDIMENSI HAM (Studi terhadap Penggusuran Kelompok Masyarakat Marginal) - Yohanes Suhardin (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
Law enforcement in the current era of globalization, but to have to uphold the rule of law, expediency, social justice must also consider human rights. Likewise, law enforcement, especially the regional regulation should consider the values social of justice and human rights. The facto, in particular law enforcement often conflict with the values social of justice and violation of human rights. PERDA (Regional Regulation of) DKI Number No. 8 of 2007 on Public order tends to conflict with the values of social justice and violation of human rights. The most of obvious human rights are violated of human rights in field of economics, sosial and cultural.